2021
DOI: 10.1155/2021/6583086
|View full text |Cite
|
Sign up to set email alerts
|

Yixintongmai Inhibits Proliferation and Migration and Promotes Apoptosis of Vascular Smooth Muscle Cells Cultured with High Glucose

Abstract: Objective. This study was designed to evaluate the effects of yixintongmai on proliferation, migration, and apoptosis of vascular smooth muscle cells (VSMCs) cultured with high glucose. Methods. VSMCs of the thoracic aorta from 5- to 8-week-old male Sprague-Dawley rats were cultured with normal (4.5 mM) or high (25 mM) glucose, respectively. The concentration of yixintongmai powder at 360 μg/ml was chosen according to pre-experimental results. Results. Yixintongmai inhibited the proliferation of VSMCs (CCK-8 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…By measuring cell viability in vitro, Shen et al examined the Buyang Huanwu decoction (BYHWD) played a vital role in protecting neurons against cerebral ischemic injury by downregulation of the expression of NOX-4 and reducing the production of ROS [ 94 ]. Guo et al [ 95 ] found that Yixingtongmai (YXTM) could inhibit the expression of matrix metalloproteinase 9 (MMP-9), nuclear factor kappa-B (NF- κ B), and B cell lymphoma-2 (Bcl-2) and stimulate the activity of caspase 3, suggesting its effects in preventing the development and progression of atherosclerosis. Wang et al [ 96 ] demonstrated that the herbal compound Tongxinluo (TXL) significantly increased myocardial capillary density and alleviated oxidative stress injury in heart failure by inhibiting the expression of NOX-4 and upregulating cardiac nitrite content and the protein expression of vascular endothelial growth factor (VEGF), p-VEGFR2, p-phosphoinositide 3-kinase (p-PI3K), p-AKT, (p-eNOS), andh oxygenase-1 (HO-1).…”
Section: Herbal Medicine: Promising Therapeutic Agents For the Modulation Of Oxidative Stress In Atherosclerosismentioning
confidence: 99%
“…By measuring cell viability in vitro, Shen et al examined the Buyang Huanwu decoction (BYHWD) played a vital role in protecting neurons against cerebral ischemic injury by downregulation of the expression of NOX-4 and reducing the production of ROS [ 94 ]. Guo et al [ 95 ] found that Yixingtongmai (YXTM) could inhibit the expression of matrix metalloproteinase 9 (MMP-9), nuclear factor kappa-B (NF- κ B), and B cell lymphoma-2 (Bcl-2) and stimulate the activity of caspase 3, suggesting its effects in preventing the development and progression of atherosclerosis. Wang et al [ 96 ] demonstrated that the herbal compound Tongxinluo (TXL) significantly increased myocardial capillary density and alleviated oxidative stress injury in heart failure by inhibiting the expression of NOX-4 and upregulating cardiac nitrite content and the protein expression of vascular endothelial growth factor (VEGF), p-VEGFR2, p-phosphoinositide 3-kinase (p-PI3K), p-AKT, (p-eNOS), andh oxygenase-1 (HO-1).…”
Section: Herbal Medicine: Promising Therapeutic Agents For the Modulation Of Oxidative Stress In Atherosclerosismentioning
confidence: 99%